Selecting and Implementing Evidence-Based Practice A Practical Program Guide - Bertram, Rosalyn; Kerns, Suzanne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
"Bertram and Kerns present a compelling imperative for evidence based practice. Selecting and Implementing Evidence-Based Practice: A Practical Program Guide is timely, cogent, masterful and forceful. [...] Advancing the evidentiary movement among practitioners, managers and academics, these authors have made an indelible contribution to our behavioural health and social service communities and to those we serve." -Katharine Briar-Lawson, PhD, LMSW, Professor and Dean Emeritus, University at Albany School of Social Welfare and National Child Welfare Workforce Institute To improve client outcomes and practitioner competence, the book clarifies practices to address common problems such as anxiety, depression, traumatic stress, and child behavioural concerns. The authors also provide examples and suggest how to integrate implementation of evidence-based practice into academic programs through collaboration with behavioural health or social service programs. Among the many topics discussed: Academic workforce preparation and curricula development Data-informed selection and implementation of evidence-based practice Anticipating and resolving practical challenges to implementation Negotiating treatment challenges with clients Collaboration between academic and behavioural health care programs This text is a valuable resource for both academic and behavioural health care programs. It will improve workforce preparation and behavioural health care service provision by helping aspiring practitioners and programs develop the necessary knowledge and skills to select, effectively implement and sustain evidence-based practice. .
Beginning with the End in Mind -- Visiting the Clinic: A Child and Family Tale -- Definitions and Debates -- Misconceptions and Facts -- Workforce Preparation: Academic Curricula and Concerns -- Establishing Effectiveness: An Innovation Tale -- An Explorer's Guide to Evidence-Based Practice -- Implementation Science: Slowing Down to Install a Practice -- Starting Small: Transformation Zones and Initial Implementation -- Trouble-Shooting Implementation Challenges -- Data-Informed Implementation -- Pathways to the Future: A Tale of Two Programs.
Keywords: Social service; Developmental psychology; Medical care; Social Work; Developmental Psychology; Health Care